Novel Multifunction Filter using Current Feedback Amplifier - Walde, Dr. Nisha; Mavi, Mr. Prashant Kumar (Discoveries in Agriculture and Food Sciences, 2021)
One configuration for realizing voltage- mode multifunction filters using current feedback amplifiers (CFOA) is presented. The proposed voltage -mode circuit exhibit simultaneously low pass and band pass filters. The proposed circuits offer the following features: No requirements for component matching conditions; low active and passive sensitivities; employing only grounded capacitors and the ability to obtain multifunction filters from the same circuit configuration.